2021
DOI: 10.3389/fendo.2021.716681
|View full text |Cite
|
Sign up to set email alerts
|

Causal Effect of Blood Pressure on Bone Mineral Density and Fracture: A Mendelian Randomization Study

Abstract: BackgroundHypertension may have some association with osteoporosis. This Mendelian randomization (MR) study aimed to explore the causal effect of blood pressure (BP) on bone mineral density (BMD), fall, and fracture.MethodsWe used the genome-wide association study (GWAS) summary data among 330,956 European-descent individuals to identify 107 single-nucleotide polymorphisms (SNPs) as the instrumental variables of BP. MR analyses of these instruments were performed on 53,236 European individuals for the associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
1
8
0
1
Order By: Relevance
“…Previous studies have shown that hypertension could increase risk of osteoporosis and osteoporotic fracture, which greatly increased the incidence of fracture or re-fracture in patients with osteoporosis and caused the higher mortality ultimately. [ 16 , 17 ] In the study of Chai et al, [ 18 ] hypertension has been confirmed to be significantly associated with osteoporosis in Chinese postmenopausal women; However, this study displayed that there was no significant association between hypertension and the all-cause death risk of osteoporosis, the possible reason was related with the included sample size. There was no doubt that the history of fractures was identified to be correlated with higher all-cause death risk osteoporosis, which was mostly consistent with the result of prior research.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have shown that hypertension could increase risk of osteoporosis and osteoporotic fracture, which greatly increased the incidence of fracture or re-fracture in patients with osteoporosis and caused the higher mortality ultimately. [ 16 , 17 ] In the study of Chai et al, [ 18 ] hypertension has been confirmed to be significantly associated with osteoporosis in Chinese postmenopausal women; However, this study displayed that there was no significant association between hypertension and the all-cause death risk of osteoporosis, the possible reason was related with the included sample size. There was no doubt that the history of fractures was identified to be correlated with higher all-cause death risk osteoporosis, which was mostly consistent with the result of prior research.…”
Section: Discussionmentioning
confidence: 73%
“…El resultado reveló que las pacientes en el grupo de osteoporosis tuvieron una mayor prevalencia de HTA (p < 0,05), asociándose significativamente. Sin embargo, He et al (26) realizaron un estudio de aleatorización mendeliana (RM) para poder hallar el efecto causal de la presión arterial (PA) sobre la densidad mineral ósea. Se realizaron análisis de RM en 53 236 genomas de individuos europeos para la asociación con la DMO del antebrazo (FA-DMO), la DMO del cuello femoral (FN-DMO) y la DMO de la columna lumbar (LS-DMO).…”
Section: La Segunda Teoría Basada En El Sraa Especialmente Conunclassified
“…[9] Many factors can improve the incidence of osteoporosis, and mainly include elderly, postmenopausal women, steroid drugs, and hyperthyroidism. [10][11][12][13][14] The decrease in calcitonin secretion after complete or subtotal thyroidectomy was proven to cause osteoporosis. [15] Increased awareness of side effects of main osteoporosis drugs such as bisphosphonates caused decreased adherence to pharmacotherapy regimes, which was highlighted as "a crisis in the treatment of osteoporosis."…”
Section: Introductionmentioning
confidence: 99%